Building a "Smiling Brazil"? Implementation of the Brazilian National Oral Health Policy in a health region in the State of São Paulo - Aline Guerra Aquilante; Geovani Gurgel Aciole (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
This paper is a case study on the implementation of the Brazilian National Oral Health Policy (PNSB), known as "Smiling Brazil", in the cities of the Regional Health Department of Araraquara (DRS III) in São Paulo State. A structured questionnaire was given to the municipal oral health coordinators, an interview with oral health care professionals and managers was conducted, and the official data provided by the Brazilian Ministry of Health were coded to assess the policy's scope: (i) expansion and qualification of actions; (ii) work conditions; (iii) care; (iv) access; and (v) planning and management. The quantitative and qualitative analyses were linked by methods triangulation. In terms of PNSB implementation, the majority of the cities (52.6%) were classified as "good", with 42.1% classified as "bad". Approximately 10 years after launching the PNSB, despite strides in oral health care and access to different levels of care, the cities still experience difficulties in implementing the policy's principles.